2009
DOI: 10.1007/s10194-009-0122-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of migraine and tension-type headache among adults in Jordan

Abstract: Here, we investigated the prevalence of headache among adults in Jordan. The study was conducted from January 2007 to November 2008. A sample of 4,836 participants were permitted to complete a self-conducted screening questionnaire. As much as 82.3% of participants complained from headache at least once per year. 36.1% were tension-type headache and 59% of the participants had other family members who suffered from headache. Headaches affected everyday activities in 51.6% of the participants; 82.7% of particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
22
4
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 37 publications
(36 reference statements)
12
22
4
1
Order By: Relevance
“…As expected, the prevalence of migraine was higher in females than in males with a ratio of 1:1.5, similar to the continental average . Migraine without aura in this study takes the higher proportion of migraine headache, which is 71.1%, and that of migraine with aura was 28.9% of migraine headache in general; this is true in most studies …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As expected, the prevalence of migraine was higher in females than in males with a ratio of 1:1.5, similar to the continental average . Migraine without aura in this study takes the higher proportion of migraine headache, which is 71.1%, and that of migraine with aura was 28.9% of migraine headache in general; this is true in most studies …”
Section: Discussionsupporting
confidence: 87%
“…Prevailing poor living conditions in the slum and stressing factors, which may precipitate/perpetuate headache such as high rates of infections, injury, and substance abuse, all may be contributory. The peak decade of migraine (30‐39 years) is similar to previously documented population‐based reports . A study from Rural Benin showed a lifetime prevalence of migraine of 4.6% and 1.8% among people aged 20‐29 and 30 and above, findings that are less than that reported in this study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…1-6, 8-11, 13 Migraine can affect people at any age but its highest prevalence was reported between ages of 35-45 years regardless of gender. [8][9][10][11]13 However, during the most reproductive years, the prevalence of migraine was reported to be threefold higher in women than in men. [13][14][15] Migraine is common in all ethnic groups.…”
Section: Introductionmentioning
confidence: 94%
“…It has been reported that the vast majority of headaches are migraine and tension-type headache (TTH). [1][2][3][4][5][6][7][8][9][10][11] Migraine is a neurovascular disorder in which cortical spreading depression, neurogenic inflammation, and cranial vascular contractile dysfunction are shared in its pathophysiology. For migraine with aura (MA), reduction in cerebral blood flow is associated with depolarization wave that propagates across the brain cortex (cortical spreading depression).…”
Section: Introductionmentioning
confidence: 99%